Site‐Selective Peptide Macrocyclization. (29th September 2020) - Wills, Rachel; Adebomi, Victor; Raj, Monika
Abstract: Cyclized peptides have seen a rise in popularity in the pharmaceutical industry as drug molecules. As such, new macrocyclization methodologies have become abundant in the last several decades. However, efficient methods of cyclization without the formation of side products remain a great challenge. Herein, we review cyclization approaches that focus on site‐selective chemistry. Site selectivity in macrocyclization decreases the generation of side products, leading to a greater yield of the desired peptide macrocycles. We will also take an in‐depth look at the new exclusively intramolecular N‐terminal site‐selective CyClick strategy for the synthesis of cyclic peptides. The CyClick method uses imine formation between an aldehyde and the N terminus. The imine is then trapped by a nucleophilic attack from the second amidic nitrogen in an irreversible site‐selective fashion. Abstract : Bye‐bye, by‐products: Macrocyclic peptides are useful in pharmaceuticals, but their synthesis is challenging due to the formation of side products. Here, we review methods for the creation of cyclic peptides in a site‐selective fashion thus minimizing side reactions. A new exclusively intramolecular, site‐selective "CyClick" strategy synthesizes cyclic peptides in high yields without generating unwanted dimers and oligomers due to intermolecular reactions.